Pediatric Robotic-Assisted Laparoscopy: A Description of the Principle Procedures - Carlo Passerotti; Craig A. Peters (The Scientific World Journal)
The advent of clinically useful robotic devices to facilitate reconstructive laparoscopic surgery in pediatric urology opens new doors to minimally invasive procedures. Previously limited by the challenge of delicate suturing and reconstruction using conventional laparoscopic instruments, robotic assistance offers a more rapid climb up the learning curve. Initial procedures that have been safely and efficaciously performed with robotic assistance include nephrectomy, partial nephrectomy, pyeloplasty, and antireflux surgeries. These techniques and their outcomes will be reviewed, as well as some of the challenges still posed by this methodology.